ON THE QUESTION OF THE MEANING OF HUMAN CAPITAL FACTOR IN THE INNOVATIVE DEVELOPMENT OF THE COUNTRY - A. A. Hokonov (Модернизация, инновация, развитие)
In article the main theoretical approaches to the concept «human capital» are stated. The structure of the human capital and a role of its parameters in the context of innovative development of the country is considered. The essence of concept the negative human capital reveals. Interest of the state in need of implementation of large-scale investments into the human capital during transformations is defined.